Analysing the effects of satisfaction on behavioural intentions about M-wallet adoption: A study on Generation Y - Nitesh Goyal; Gurvinder Singh; Geetanjali Thakur (Rajagiri Management Journal (RAMJ), 2025)
The purpose of this study is to examine respondents' behavioural intentions towards m-wallets. The study tries to explain the effect of perceived usefulness, perceived ease of use and security on satisfaction, further leading to behavioural intention.The TAM model served as the foundation for a research model. A self-administered questionnaire was designed using standardized scales. A survey was conducted among generation Generation Y of Chandigarh. The questionnaires were sent through Google Forms. A total of 250 questionnaires were distributed, out of which only 224 were received. Furthermore, an SEM model was developed to analysed the data using IBM SPSS.The model was studied in two parts, i.e. firstly, the factors which impact consumer satisfaction and further leading behavioural intention. The results showed that PEOU and PS had a positive and significant impact on consumer satisfaction, while PU had no impact on customer satisfaction. It was also found that satisfaction has a positive relation with behavioural intention. Further analysis showed that Google Pay was the most preferred mobile wallet, followed by PayTm and PhonePe. The descriptive data provided that the main reasons for their preference were convenience and time-saving features.Firstly, the findings of the study are limited to Generation Y, which cannot be generalized to all age groups. Secondly, only M-wallets are considered; therefore, in the future, other forms of digital payment methods can be studied. The study is primarily adapted from the TAM model. However, the literature also indicates other theories also, such as the UTAUT model and the theory of planned behaviour, which can be integrated to study the relationship between technology usage and the behaviour of customer towards technology.The findings suggest that the marketers should focus on the usefulness and security of M-wallets. PU is related to the degree to which individuals trust that adopting a certain system will improve their work performance. The research provides in-depth knowledge/understanding about m wallets and factors affecting the behavioural intention of consumers towards M-wallets.The majority of previous studies exclusively focused on the TAM/UTAUT model, whereas this paper studied satisfaction as a predicator of behavioural intention.
Keywords: 650; Mobile wallet; E-banking; TAM model; Consumer behaviour; Satisfaction; Intention